2001
DOI: 10.1088/0953-4075/34/9/101
|View full text |Cite
|
Sign up to set email alerts
|

Electron spectrometry at the µeV level and the electron affinities of Si and F

Abstract: Photodetachment microscopy of the negative ions Si- and F- has made it possible to measure the electron affinities of silicon and fluorine with improved accuracy. The new recommended electron affinities of 28Si and 19F are 11 207.252(18) and 27 432.446(19) cm-1, i.e. 1.389 5220(24) and 3.401 1895(25) eV, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
104
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(124 citation statements)
references
References 26 publications
18
104
0
2
Order By: Relevance
“…24 The ionization energy and electron affinity of Li and F are 5.39 and In all but the rinsed, discharged sample ͑127D _ rinsed͒ a broad peak is seen at approximately 18 ppm, which corresponds to the chemical shift of the anion receptor salt, suggesting at least partial co-intercalation of the anion receptor. −3.40 eV, 25,26 respectively ͑the values calculated in this work were 5.62 and −3.54 eV, respectively͒. The solvation of Li + and F − in PC were calculated to be −135.16 and −94.36 kcal/mol.…”
mentioning
confidence: 52%
“…24 The ionization energy and electron affinity of Li and F are 5.39 and In all but the rinsed, discharged sample ͑127D _ rinsed͒ a broad peak is seen at approximately 18 ppm, which corresponds to the chemical shift of the anion receptor salt, suggesting at least partial co-intercalation of the anion receptor. −3.40 eV, 25,26 respectively ͑the values calculated in this work were 5.62 and −3.54 eV, respectively͒. The solvation of Li + and F − in PC were calculated to be −135.16 and −94.36 kcal/mol.…”
mentioning
confidence: 52%
“…These EAs are comparable to the CCSD + F12 + "high level correction" value (3.4276 eV) 41 and the experimental value (3.401 eV). 42 Table 1 Conformations of Si 2 H 4 . As a result of the relative weakness of silicon π-bonds, unsaturated silicon hydrides have many physical dissimilarities compared to analogous hydrocarbons.…”
Section: ■ Resultsmentioning
confidence: 99%
“…0.1−0.2 eV. First, although it is not accurate to equate an AE 298 to the enthalpy of the corresponding unimolecular reaction at 298 K because of thermal effects, 26 28 In calculations for F − , we use the value of −249 using the electron affinity (EA) reported by Blondel et al, 29 and for F 2 − , the value of −301 which uses the EA reported by Artau et al 30 The values used for Cl − , Br − and I − are −227, −213, and −188, respectively, which use experimental EAs from a recent review paper. 31 For CF − we use a value of −63, using the EA(CF) = 3.3 ± 1.1 eV (reported as a lower limit), 32 and for CF 2 − a value of −199 which uses the EA(CF 2 ) = 0.179 ± 0.005 eV.…”
Section: Thermochemistry: General Commentsmentioning
confidence: 99%